(untitled) (International Conference on Computers in Education, 2020)
The generation of learning strategies is related to students’ cognitive abilities, and students with similar cognitive abilities tend to adopt similar learning strategies. This study conducted an experiment of a system programming course with 113 college students and collected logs from a learning management system. There are five learning strategies that can be identified through sequence clustering analysis, they are comprehensive video-oriented learning, comprehensive slide-oriented learning, offline learning, selective learning, and reflective learning. Among the five learning strategies, selective learning strategy is positively correlated with students’ cognitive load, which can be explored that these students make practice of quiz without reading learning materials, and tend to select unfamiliar concepts to read based on quiz results. Students who use selective learning strategy are referred to as incomprehensive learners, and the selective learning strategy prone to increase students’ cognitive load due to overflying unclear and segmented information.